The Italian Observatory on Food Surplus, Recovery, and Waste: The Development Process and Future Achievements - Grant, Federica; Rossi, Laura (Frontiers in Nutrition, 2022)
Food loss and waste (FLW) is an environmental, social, and economic problem. Countries all around the world are looking for efficient strategies to prevent and reduce FLW, as recommended by target 12.3 of the Sustainable Development Goals (SDGs) of the United Nations. The European Union (EU) is strongly committed to helping solve the FLW issue, setting up the Platform on Food Losses and Food Waste, and adopting the Farm to Fork Strategy. Italy has also adopted a consolidated approach toward this issue, in particular through the redistribution of food surplus to those in need, a policy that was instituted with the Gadda Law 166/2016. Importantly, this normative framework also provided for the establishment of the National Observatory on Food Surplus, Recovery, and Waste [Osservatorio sulle Eccedenze, i Recuperi e gli Sprechi Alimentari (OERSA)]. This article describes the creation and development of the OERSA, as the technical entity supporting national FLW policies. One of the first actions taken by the OERSA was that of mapping the FLW initiatives that were being implemented along the entire food supply chain in Italy. This gave the OERSA a solid foundation on which to begin working on two different fronts: (1) Collecting data regarding the primary production sector and at the consumer level and (2) Establishing educational programs and awareness campaigns. The data collected by the OERSA highlight that, although several actors of the Italian supply chain are already conscious of the causes of FLW, new strategies that focus on innovation and cooperation should be encouraged.